2015
DOI: 10.1016/j.immuni.2015.06.021
|View full text |Cite
|
Sign up to set email alerts
|

An Interleukin-33-Mast Cell-Interleukin-2 Axis Suppresses Papain-Induced Allergic Inflammation by Promoting Regulatory T Cell Numbers

Abstract: SUMMARY House dust mite-derived proteases contribute to allergic disorders in part by disrupting epithelial barrier function. Interleukin-33 (IL-33), produced by lung cells after exposure to protease allergens, can induce innate-type airway eosinophilia by activating natural helper (NH) cells, a member of group 2 innate lymphoid cells (ILC2), to secrete Th2 type-cytokines. Because IL-33 also can induce mast cells (MCs) to secrete Th2 type-cytokines, MCs are thought to cooperate with NH cells in enhancing prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
246
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(258 citation statements)
references
References 42 publications
9
246
0
3
Order By: Relevance
“…CD73-dependent adenosine generation in Tregs also promoted acute lung injury resolution [32]. Tregs limited injury by decreasing allergic airway inflammation and epithelial barrier disruption in house dust mite-derived protease induced-allergic disorders [33]. In addition, Tregs participate in the maintenance of intestinal homeostasis following damage or inflammation or infection [34-36], which has been well reviewed [37].…”
Section: Treg-mediated Repair At Multiple Tissuesmentioning
confidence: 99%
“…CD73-dependent adenosine generation in Tregs also promoted acute lung injury resolution [32]. Tregs limited injury by decreasing allergic airway inflammation and epithelial barrier disruption in house dust mite-derived protease induced-allergic disorders [33]. In addition, Tregs participate in the maintenance of intestinal homeostasis following damage or inflammation or infection [34-36], which has been well reviewed [37].…”
Section: Treg-mediated Repair At Multiple Tissuesmentioning
confidence: 99%
“…The many functions of ILC2s in the context of models of allergic disease suggest that ILC2 populations might represent a fruitful therapeutic target. It is also possible that negative regulators of ILC2 responses such as type 1(79) and type 2 interferons(80), IL-27(81, 82), KLRG1 signaling by E-cadherin(66), lipoxin A4(83), and T regulatory cells(84, 85) could also be manipulated to reduce ILC2 activation in the context of allergic inflammation.…”
Section: Innate Immunitymentioning
confidence: 99%
“…Supporting the critical role of IL-33, anaphylaxis was blocked by treating mice with an IL-33 receptor antagonist prior to oral challenge and could not be restored in mice lacking IL-33 receptor [54]. Using bone marrow-derived mast cells, previous groups showed that IL-33-stimulated mast cell signaling promotes expansion of T regulatory (Treg) cells in an IL-2-dependent fashion [55]. Given these findings came from in vitro work, the IL-33/Th2 pathway may be confined to tissue-resident mast cells.…”
Section: Th2 Immune Activation By Skin Allergensmentioning
confidence: 99%